2022
DOI: 10.3389/fnut.2021.784018
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the EAT-Lancet Diet Pattern and Risk of Type 2 Diabetes: A Prospective Cohort Study

Abstract: Background:The EAT-Lancet Commission has promulgated a sustainable dietary guideline and recommended that it was designed to improve the human health and support environmental sustainability.Objective:This research was designed to explore the association between this healthy diet pattern (EAT-Lancet diet pattern, EAT-LDP) and risk of type 2 diabetes (T2D).Methods:Between 2006 and 2010, a total of 59,849 participants from the UK Biobank without diabetes, cardiovascular disease, or cancers were included at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 47 publications
4
43
0
Order By: Relevance
“…The current study meaningfully extends the literature by showing that adiposity, as indicated by BMI and WC, is indeed a mediator for fish diets. This finding mirrors a study conducted on healthy diet patterns and the risk of type 2 diabetes that concluded adiposity was a sizeable mediator 37 . Further studies should explore other potential mediators, such as blood pressure and lipid profile.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The current study meaningfully extends the literature by showing that adiposity, as indicated by BMI and WC, is indeed a mediator for fish diets. This finding mirrors a study conducted on healthy diet patterns and the risk of type 2 diabetes that concluded adiposity was a sizeable mediator 37 . Further studies should explore other potential mediators, such as blood pressure and lipid profile.…”
Section: Discussionsupporting
confidence: 82%
“…This finding mirrors a study conducted on healthy diet patterns and the risk of type 2 diabetes that concluded adiposity was a sizeable mediator. 37 Further studies should explore other potential mediators, such as blood pressure and lipid profile.…”
Section: The European Prospective Investigation Into Cancer and Nutri...mentioning
confidence: 99%
“…A healthy diet pattern potentially interactive and cumulative associations of different dietary components, and could reflect the numerous and multifaceted combinations of nutrient and food consumption [ 24 ]. Several published observational studies have found a beneficial effect of greater adherence to a healthy diet pattern on CMDs [ 25 28 ]. Randomised controlled trials have also strengthened the beneficial impact of physical exercise and healthy diet on cardiorespiratory fitness, and cardiometabolic health in adults [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some previous studies have assessed the mediating role of weight change using total energy intake-adjusted estimates for foods or dietary variables (for example [2][3][4] ). As the energy-adjusted estimate implies an isocaloric comparison of foods or diet compositions at that time point, it is unclear how changes in weight would be achieved under this model.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have assessed a potential mediating role of BMI (or weight change, as the modelling implies that a change in diet would cause a change in weight) with regards to diet and disease using observational data. [2][3][4] It is well known that adjustment for total energy intake in these analyses implies an isocaloric comparison between diets, that is, the average relative causal effect of the exposure. 5 Studies can also consider the effect of increasing intake of some foods or macronutrients on top of the usual diet, that is, the total causal effect.…”
Section: Discussionmentioning
confidence: 99%